The Comparsion of the Efficacy of Group Psychotherapy Based on Acceptance and Commitment Therapy, and Mindfulness on Craving and Cognitive Emotion Regulation in Methamphetamine Addicts - Ahmadreza Kiani; Nezamaldin Ghasemi; Ali Pourabbas (Drug Control Headquarters, Research and Education Office, 2013)
Aim: Today, third wave therapies in psychotherapy shift their attention from challenging cognitions to awareness and acceptance of feelings, emotions, cognitions and behaviors. Therefore, this research aimed to compare of efficacy of group psychotherapy based on acceptance and commitment therapy, with mindfulness on craving and cognitive emotion regulation in methamphetamine addicts. Method: Research method was semi experimental research design with pre-post test and follow up. The population of research was included all of methamphetamine addicts in baharestan, Isfahan. Drug abusers was 34 participants that refered to addiction rehabilitation centers and selected by snowball sampling and finaly divided to 2groups by radomization (acceptance and commitment therapy group and mindfulness groups). Each groups recieved treatment in 12 sessions (At First 2 sessions per week and at last 1 session per week). Two groups assessed by craving test (Ekhtiary, 1387) and cognitive emotion regulation (garnefski et al, 2002), in pretest, post test and follow up. Results: The results showed that two treatment groups had significant effect on craving intensity in post test and follow up. In addition, there was no significant difference in comparing of the efficacy of these two treatments on cognitive emotion regulation and it means that both two traetments had same effect on cognitive emotion regulatin. Conclusion: we can say that acceptance and commitmet therapy and mindfulnesshave effect on reduction psychopathology from using amphetamines due to same theraputic factors.